Evaluating Quasi Random Deployment in Zigbee Based Wireless Sensor Networks - Itu Snigdh; Nisha Gupta (Institute of Advanced Engineering and Science, 2015)
Among the various parameters and constraints considered that are affected by optimal deployments, performance as per the mac layer has attained limited attention. This article is aimed at two things. Firstly, it aims to understand the packet delivery parameters for convergecast communication pattern ideal for Zigbee based wireless sensor networks. Secondly, it aims to suggest enhancements through proposing a quasi based deployment pattern, that may help boost the performance to acceptable levels. We simulate and observe the packet based statistics at the mac layers employing different protocols like AODV, DSR. This paper is also an effort to suggest the use of Quasi based deployment strategy comparable to the existing random and deterministic methods. The inferences obtained are for zigbee networks encorporating both peer to peer (using a tree based topology) and star (using a graph based topology) WSN architectures. A quasi based deployment pattern offers scope for improvement of the reliability metrics which is the sole accountability of the mac layer, irrespective to the protocol employed at the higher levels or the backbone structure for communication. DOI: http://dx.doi.org/10.11591/telkomnika.v15i1.8074